Treatment effect estimates in multi-arm multi-stage (MAMS) clinical trials - Choodari-Oskooei, Babak (Henry Stewart Talks, 2020)
Introduction to MAMS clinical trials, MAMS designs with an intermediate outcome, TAMS setting, Definition of selection bias in treatment effect estimates, Impact of stopping rules in MAMS designs, Quantifying potential bias using simulations and real trials, Methods to reduce bias